BS EN IEC 60404-8-3. Magnetic materials. Part 8-3. Specifications for individual materials. Cold-rolled electrical non-alloyed and alloyed steel sheet and strip delivered in the semi-processed state (9th July 2021) - British Standards Institution,
No abstract available